Optimalisasi Pelayanan Sekretariat KPU kepada Komisioner KPU dalam Menyelenggarakan Pemilihan Umum - R., Karina Rahmiz A.; Yasin, H. M. (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to determine the role of the General Election Commission Secretariat of Bone Regency, especially in improving the quality of the apparatus that is reliable, professional, and proportional, to provide optimal service to the General Election Commission Commissioners in holding general elections. This study also aims to determine what factors influence the General Election Commission Secretariat's services to General Election Commission Commissioners is holding General Elections. This study uses empirical research methods. Data obtained directly from the object of research in the field through observations and interviews with informants. The data is processed and analyzed qualitatively. The results obtained indicate that the services provided by the General Election Commission Secretariat of Bone Regency are based on Law No. 7 of 2017, namely facilitating the General Election Commission Commissioners of Bone Regency in organizing the General Election following its main function is to provide services, including a. administrative services which include correspondence, reporting, and accountability; b. services in the financial sector, which include the preparation and formulation of budgets according to the Election's needs, receiving, spending, and being accountable following statutory regulations; and c. services in the field of infrastructure include election logistics, managing and maintaining General Election Commission assets and inventory, and maintaining all facilities owned by the General Election Commission. The factors that affect the Bone Regency General Election Commission Secretariat services in facilitating the Bone Regency General Election Commission Commissioners so that they have not achieved optimal results are influenced by human resources, work environment, and geographical or natural factors.